Importance of high power factor in thermoelectric materials for power generation application: A perspective. (15th January 2016) - Liu, Weishu; Kim, Hee Seok; Jie, Qing; Ren, Zhifeng
Graphical abstract: Abstract: The figure of merit ( ZT ) has been used for more than half a century to guide the research of thermoelectric materials. In this perspective viewpoint, we emphasize that the power factor ( PF ) is more important than the thermal conductivity for thermoelectric power generation for a given ZT . We also propose the newly defined engineering parameters ( ZT ) eng and ( PF ) eng are the more practical indicators to show the temperature dependent efficiency and output power, as compared with conventional ZT and PF .